Selecting the optimal treatment for left main coronary disease: The importance of identifying subgroups of patients. Issue 12 (28th September 2022) - Seco, Michael; Paterson, Hugh S.; Gaudino, Mario; Vallely, Michael P.
Abstract: Randomized trials of stenting versus surgery for patients with unprotected left main (LM) coronary stenosis have largely shown similar survival between the two interventions. However, patients with LM stenosis represent a heterogeneous group in which subgroups likely to benefit from one therapy more than another are difficult to identify. Increasing coronary disease burden is the most accepted subgrouping for identifying optimal therapy but this can be defined in more detail allowing greater discrimination. Competitive flow reduces bypass graft patency in patients with isolated LM stenosis and complex bifurcation stenoses reduce the effectiveness of coronary stenting. The evidence for LM stenosis subgroupings is presented.